2009
DOI: 10.1097/cji.0b013e31819aa31e
|View full text |Cite
|
Sign up to set email alerts
|

Mutual Helper Effect in Copulsing of Dendritic Cells With 2 Antigens

Abstract: To develop an efficient dendritic cell (DC)-based immunotherapy protocol, we examined whether simultaneous pulsing of DCs with a given antigen and a third-party antigen could enhance their antigen presentation capacity. Purified splenic DCs of Balb/c mice were pulsed separately with immunoglobulin G, ovalbumin, conalbumin, P15 peptide of Mycobacterium tuberculosis, and prostate-specific antigen or double combinations of the aforementioned antigens. In some settings, DCs pulsed with 1 antigen were mixed equally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 45 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…Accordingly, in an immunotherapeutic study, it was indicated that utilization of a Th0- or Th2-inducing helper Ag, would in fact serve the needs of tumor cells, rather than prevent tumor growth [ 13 ]. In the current study, we did not determine the type of T cell–mediated responses; however, as mentioned earlier, in our previous study we observed that OVA-pulsing of DCs would shift T-cell responses towards Th1 [ 12 ]. In this regard, Eriksson et al [ 23 ], in two DC-based studies, reported that conjugation of the helper Ag to the target Ag could lead to more pronounced antitumor responses as compared to simply mixing the Ags [ 24 ].…”
Section: Discussionmentioning
confidence: 84%
See 4 more Smart Citations
“…Accordingly, in an immunotherapeutic study, it was indicated that utilization of a Th0- or Th2-inducing helper Ag, would in fact serve the needs of tumor cells, rather than prevent tumor growth [ 13 ]. In the current study, we did not determine the type of T cell–mediated responses; however, as mentioned earlier, in our previous study we observed that OVA-pulsing of DCs would shift T-cell responses towards Th1 [ 12 ]. In this regard, Eriksson et al [ 23 ], in two DC-based studies, reported that conjugation of the helper Ag to the target Ag could lead to more pronounced antitumor responses as compared to simply mixing the Ags [ 24 ].…”
Section: Discussionmentioning
confidence: 84%
“…In particular, numerous studies have attempted to fully exploit the potential of potent ex vivo –generated antitumor DCs in order to elicit efficient T-cell responses [ 21 ]. In our previous study, we showed that the presence of a helper Ag next to the target Ag during pulsing of DCs could enhance the proliferation rate of CD8 T cells specific to both the helper and target Ags, a phenomenon we termed “mutual helper effect” [ 12 ]. In this study, elucidate the in vivo effectiveness of this approach against tumor, we vaccinated a murine model of colon cancer with DCs pulsed with the combination of a helper Ag (OVA) and a tumor Ag (AH1).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations